Braudel´s model of historical structures and interpretative significance to teach church history in the Slovak school system - PaedD, ThLic.; Genčúrová, Gabriela (IJRDO- Journal of Educational Research, 2016)
This thesis presents the theory of temporalities of F. Braudel as method of new interpretation of historical time. It also pplies a new interpretation of historical time of space and events to the reading History of Church within the subject relegious education. Within the meaning of Braudel model structuring of time and events in history it demonstrates the possibilities of a new way of interpretation church-historical subject matter. Braudel´s modification of tructuring time for educational purposes proves by concrete proposal of interactive didactic tool called timeline „Longue durée“ as well as it supports application of Braudel´s of temporalities into the teaching of Relegious education.